Daily Brazilian green propolis intake elevates blood artepillin C levels in humans. (16th February 2021) - Ding, Jiangli; Matsumiya, Tomoh; Hayakari, Ryo; Shiba, Yuko; Kawaguchi, Shogo; Seya, Kazuhiko; Ueno, Kayo; Imaizumi, Tadaatsu
Abstract: BACKGROUND: Propolis is a natural product collected by worker bees from a variety of plant species. As a type of propolis, Brazilian green propolis contains a large amount of artepillin C. Artepillin C is a cinnamic acid derivative and has been shown to have a wide variety of biological functions, including anti‐inflammatory, antiviral and antitumor activities, in both cell culture and animal models. However, how propolis is digested and absorbed remains to be elucidated. Moreover, blood artepillin C levels after propolis intake have not been shown in human studies. RESULTS: A randomized, single‐blind placebo‐controlled study on the effect of Brazilian green propolis on serum artepillin C levels was conducted with healthy volunteers. The participants ( n  = 133) were randomly allocated in an approximately 2:1 ratio to two groups: propolis ( n  = 91) and placebo ( n  = 42). The participants took daily propolis or placebo, and blood tests were performed on day 0 (before propolis intake) and days 1, 3 and 7. Artepillin C was detected in serum in almost all individuals in the propolis groups. No serum artepillin C was detected in the placebo group. Serum artepillin C levels in the female group tended to be higher than those in the male group. In the female group, menstrual status was unrelated to serum artepillin C levels. CONCLUSION: These results suggested that propolis intake might be more effective for females than for males. © 2021 Society of Chemical Industry